A review on Thermal Properties of Polymer Composite Materials - Sanjay Soni, (AG Volumes, 2022)
Across the globe, scientists and engineers are focusing their attention on hybrid polymer composites because of the unique opportunities they provide for solving pressing material challenges. Polymers and hybrid composites are developing as versatile replacements to metals and their alloys in many conventional and innovative technical applications. Hybrid composites need extensive testing due to variations in temperature and mechanical loads. Hybrid composites degrade and alter characteristics when subjected to extremes of temperature, such as those found in the environment. To improve the mechanical and thermal qualities of structures, carbon fibre composites are increasingly being employed in place of reinforcing bars or concrete. The thermal property values of hybrid polymer composites made with various filler materials will change depending on the temperature. After reading this paper's overview on the thermal characteristics of fibre-reinforced hybrid composite materials, I realised that there is still a lot of room for investigation into the study of composite materials' thermal properties, particularly those made using Silicon oxides, aluminium oxides, carbon, and graphite as filler material in conjunction with glass fibre and natural fibres. This literature review demonstrates that hybridization has a positive influence on the thermal characteristics of fiber-reinforced hybrid composite materials.